2020
DOI: 10.3892/or.2020.7742
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA PLK1S1 was associated with renal cell carcinoma progression by interacting with microRNA‑653 and altering C‑X‑C chemokine receptor 5 expression

Abstract: Renal cell carcinoma (RCC) is the most common type of renal cancer. Long non-coding RNA (lncRNA) has been reported to play a vital role in the development and progression of various types of cancer type. However, the underlying molecular mechanisms of PLK1S1 in regulating RCC progression remain unclear. In the present study, PLK1S1 was upregulated in RCC tissues and cells, and PLK1S1 expression was also significantly elevated in stage IV RCC tissues. Kaplan-Meier analysis showed that patients with high PLK1S1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…miR-653 was implied to be an anti-tumor gene in some cancers. For example, lncRNA PLK1S1 expedited renal cell carcinoma cell viability and invasion by absorbing miR‑653 and altering CXCR5 level [ 35 ]. Moreover, circHIPK3 facilitated gastric cancer metastasis through interacting with miR-653 and miR-338-3p to modulate NRP1 expression under hypoxia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-653 was implied to be an anti-tumor gene in some cancers. For example, lncRNA PLK1S1 expedited renal cell carcinoma cell viability and invasion by absorbing miR‑653 and altering CXCR5 level [ 35 ]. Moreover, circHIPK3 facilitated gastric cancer metastasis through interacting with miR-653 and miR-338-3p to modulate NRP1 expression under hypoxia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLK1s1 is reported as a one of the most promising genes associated with Attention-deficit hyperactivity disorder (ADHD) [53]. Another study revealed that PLK1S1 promoted (Renal cell carcinoma) RCC tumorigenesis and enhanced sorafenib resistance of RCC through the miR-653/CXCR5 pathway [54].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to miR-146b-5p, miR-653 plays different roles in different cancers. It appears to function as a tumor suppressor in most malignant tumors, such as renal cell carcinoma, melanoma, gastric cancer, cervical cancer, breast cancer, Wilms' tumor and non-small cell lung cancer [32][33][34][35][36][37][38], but it was also reported to act as an onco-miRNA in prostate cancer and bladder cancer [39,40]. Regardless, our meta-analysis indicated that miR-653 was downregulated in pancreatic cancer, suggesting that it might suppress pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%